Interest in Visiting Leading Tourist Destinations in Jakarta - Oktavia, Reno Catelya Dira; Gantina, Devita; Pusparani, Pusparani; Festivalia, Filma; Marie, Andhalia Liza (Jurnal Penelitian Pariwisata, 2023)
This study aims to determine the effect of tourist attraction, social media promotion, and accessibility on visiting intentions through tourist satisfaction. This type of research is descriptive quantitative with multiple regression analysis methods. This population is all visitors who come to leading destinations in Jakarta. The sample in this study was 150 respondents. The sampling technique used accidental sampling, which met directly with the researcher. The results showed that: (1) Partially tourist attraction, social media promotion, and accessibility have a significant effect on tourist satisfaction (2) Partially tourist attraction, social media promotion, accessibility, and tourist satisfaction have a significant effect on interest in visiting; (3) Partially, tourist attraction, social media promotion, and accessibility have a significant effect on visiting intentions through tourist satisfaction. Suggestions that can be taken into consideration are as follows: (1) Managers of leading tourist destinations continue to improve the best quality of service for tourists; (2) The Regional Government of the City of Jakarta continues to improve public transportation facilities that are well integrated. Keywords: Tourist Attraction, Social Media Promotion, Accessibility, Tourist Satisfaction, Visiting Interests